A comparative study of articular cartilage thickness in the stifle of animal species used in human pre-clinical studies compared to articular cartilage thickness in the human knee - Frisbie, D. D.; Cross, M. W.; McIlwraith, C. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Histological measurements of the thickness of non-calcified and calcified cartilage, as well as the subchondral bone plate in five locations on the femoral trochlea and medial femoral condyles of species were used in preclinical studies of articular cartilage and compared to those of the human knee. Cadaver specimens were obtained of six human knees, as well as six equine, six goat, six dog, six sheep and six rabbit stifle joints (the animal equivalent of the human knee). Specimens were taken from the lateral trochlear ridge, medial trochlear ridge and medial femoral condyle. After histopathological processing, the thickness of non-calcified and calcified cartilage layers, as well as the subchondral bone plate, was measured. Average articular cartilage thickness over five locations were 2.2–2.5 mm for human, 0.3 mm for rabbit, 0.4–0.5 mm for sheep, 0.6–1.3 mm for dog, 0.7–1.5 mm for goat and 1.5–2 mm for horse. The horse provides the closest approximation to humans in terms of articular cartilage thickness, and this approximation is considered relevant in pre-clinical studies of cartilage healing.
Keywords: Reticular cartilage thickness; stifle